Jenderal AH. Nasution dalam Peristiwa 17 Oktober 1952 - Endang Fathurrahman; Ahmad Sugiri; Yanwar Pribadi (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2018)
The Indonesian National Army was realized because of the desire of the people, especially the youth, who felt called to fight for the independence of the Indonesian state that had been proclaimed. In 1947, the paramilitary forces and the TRI in the national army were united, under the name of the Indonesian National Army (TNI). In 1950-1952 General A. H. Nasution was appointed as Army Chief of Staff, in his leadership the 17 October 1952 incident occurred when he submitted a proposal to the president to dissolve parliament. But this event also occurred because of parliamentary efforts to interfere in military affairs, and the Army at that time faced a crisis that could escalate towards division.